SUSTAINABLE ECOSYSTEM AND ENVIRONMENTAL MANAGEMENT IN INDIA - Prof. Vijay K. More, Dr. Sagarraj Rohidas Chavan (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Sustainable ecosystems and effective environmental management are critical for ensuring the long-term health and resilience of natural resources, which are vital for human well-being and economic stability. In India, a country characterized by diverse ecosystems and rapid economic growth, the challenges of maintaining ecological balance and managing environmental issues are particularly pronounced. This research paper aims to explore the significance of sustainable ecosystem practices and environmental management strategies within the Indian context. It examines the current state of environmental management, assesses the effectiveness of existing policies, and identifies key challenges and opportunities for improvement. Using a combination of literature review, case studies, and policy analysis, the study reveals that while India has made significant strides in implementing environmental policies and management practices, there remain substantial obstacles related to governance, social factors, and technical limitations. The findings suggest that enhancing policy frameworks, fostering community engagement, and leveraging technological innovations are essential for achieving more sustainable outcomes. The research concludes that a comprehensive and integrated approach to environmental management is crucial for addressing India's complex environmental challenges and ensuring the sustainability of its ecosystems.